The firms' debt reversibility trend: An application to a large sample of industrial SMEs - António Carvalho; Filipe Sardo; Luís Dias Pacheco (Cogent Economics & Finance, 2023)
The corporate debt reversibility analysis can be carried out not only from the owner/manager's active intervention perspective but also from the perspective of a mechanical reversion, independent of owner/managers' deliberations. Our study aims to discover how and which theoretical perspective underlying reversibility has the most significant impact on the capital structure of Portuguese industrial small and medium-sized enterprises (SMEs). The present paper proposes a new approach linking the measures commonly used to determine the target leverage level to the specific assumptions of theories addressing debt dynamics. Our results show that the perspective with the stronger impact on capital structure materialises in the dynamic trade-off theory assumptions. However, owners/managers also strongly consider the industry references to which firms belong. The perspective of mechanical debt reversion also contributes, at its level, to the firms' debt permanent reversibility in the sense of possible long-term stationarity.
Keywords: 330; corporate herd behaviour theory; debt reversibility; mechanical mean reversion; stationarity; target debt measures (proxies); trade-off theory